Teachers’ implementation of Competence Based Curriculum in Tanzanian public and private secondary schools: A scoping review - Revocatus C Kuluchumila (My University, 2025)
Competency-based curriculum (CBC) is about learner’s ability to apply knowledge, skills, values, and attitudes properly in definite contexts. The scoping review aimed to investigate the degree to which implementation of the CBC has been researched to address gaps in public and privately owned schools. Research findings revealed that, first, some teachers implemented the CBC effectively due to either in-service or off-the-job training. Second, number of challenges revealed include, shortage of text- books, large class size, lack of finance for offering seminars and workshops to teachers, curriculum overload, learners’ English language barriers. Third, benefits linked to training include, reducing teachers’ stress and turnover, improving teachers’ effectiveness, improvement of teaching strategies, and reducing teachers’ exhaustion. Strangely, tutors understood CBC differently, some as an application-oriented curriculum, others as an activity-based curriculum. It was generally concluded that implementation of the CBC in schools is still daunting.
Book focusing on various research done on Competence Based Curriculum and the way teachers are implementing it.
Keywords: Competency-based curriculum; scoping review; in-service training; off-service-training; public and private secondary schools; challenges facing teachers; inclusion and exclusion criteria.